Strategi Atasi Perilaku Menarik Diri di Perusahaan Rintisan Berbasis Teknologi (Technopreneur): Mengubah Tantangan jadi Peluang dengan Mendesain Ulang Pekerjaan Sendiri - Tasya Augustiya; Novia Astuti Dewi (Indo Publishing, 2026)
The issue of withdrawal behavior is critical because it disrupts productivity and stability in technology-based startups. This study aims to determine whether the ability to redesign one’s own work plays a role in addressing withdrawal behavior among employees in technology-based startups. This quantitative study of technology-based startups employed a simple linear regression approach and was conducted among 202 employees of startups in Indonesia. The research instruments included the Job Crafting and Organizational Withdrawal Behavior scales, which have been validated for reliability and validity. The results of the data analysis indicate that employees’ ability to redesign their own work significantly influences withdrawal behavior. In other words, the higher an employee’s ability to redesign their own work, the lower the level of withdrawal behavior exhibited. Thus, the conclusion of this study indicates that the level of an employee’s ability to redesign their own work in technology-based companies can reduce withdrawal behavior and has proven to be an effective strategy for addressing withdrawal behavior in the workplace of startups.